1991
DOI: 10.1515/jpme.1991.19.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Single dose of labetalol in hypertensive pregnancy: Effects on maternal hemodynamics and uterine and fetal flow velocity waveforms

Abstract: The short-term effect of 0.8 mg/kg of an intravenous bolus of labetalol on maternal and fetal hemodynamics was investigated in ten women with pregnancy-induced hypertension. The maximum effect occurred within 35 minutes after labetalol administration. At that point, the mean arterial pressure had decreased by 18% and there was a slight decrease in maternal heart rate. As to flow velocity waveforms, no significant change was found in mean systolic/diastolic (S/D) ratio of the uterine artery, umbilical artery or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A possible explanation for this increase may be labetalol-induced vasodilation impairing cerebral autoregulation, as proposed by Caicedo et al [17]. Other studies on fetal and maternal CBF were not able to demonstrate labetalol-induced changes [18,19]. However, a decrease in maternal cerebral perfusion pressure was found and suggested to result from an autoregulatory cerebral response to systemically lowered blood pressure by labetalol [19].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this increase may be labetalol-induced vasodilation impairing cerebral autoregulation, as proposed by Caicedo et al [17]. Other studies on fetal and maternal CBF were not able to demonstrate labetalol-induced changes [18,19]. However, a decrease in maternal cerebral perfusion pressure was found and suggested to result from an autoregulatory cerebral response to systemically lowered blood pressure by labetalol [19].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous labetalol was given and maximum effect occurred within 35 minutes after labetalol administration and no significant change was observed in colour Doppler indices which are in accordance to present study in which only 2 patients on labetalol therapy showed decrease in PI and RI of uterine artery and rest of the 7 patients did not show any significant changes. 9 Mahmoud et al studied effects of oral labetalol therapy in 41 patients with moderate to severe PIH. The mean systolic BP and diastolic BP on entry were 154±7 mmHg and 105±5 mmHg and all had significant proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term effect of 0.8 mg/kg of an intravenous bolus of labetalol on maternal and fetal hemodynamics was investigated in 10 women with pregnancy-induced hypertension. 12 The maximum effect occurred within 35 min after labetalol administration. The mean arterial pressure decreased by 18% and there was a slight decrease in maternal heart rate.…”
Section: Sympatholytic Drugsmentioning
confidence: 95%